KINERJA KEPALA SEKOLAH DI SEKOLAH MENENGAH KEJURUAN PEKANBARU - Maharani (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to identify and formulate indicators of emotional intelligence (olah rasa) as part of the principal's performance assessment through a case study of mediation at SMK Labor Pekanbaru. The study used a descriptive-exploratory single-case study design with the principal (KS-1), a teacher, and a parent as subjects. Data were obtained through mediation session observations, semi-structured interviews, and a review of related documents. The results indicate that KS-1 implemented three key practices of emotional intelligence (olah rasa)—active listening, empathetic paraphrasing, and neutral summarizing—that contributed directly to reducing emotional tension and achieving follow-up agreements in the form of developing classroom communication SOPs. Thematic analysis yielded five measurable indicators of emotional intelligence (olah rasa): listening without interrupting, empathetic paraphrasing, neutral summarizing, follow-up agreements, and giving appreciation. These indicators proved relevant to complement the Principal Performance Assessment (PKKS) instrument, which has previously focused more on administrative aspects. These findings confirm that emotional intelligence (olah rasa) is a leadership competency that can be observed through authentic evidence and has a direct impact on improving the quality of communication and relationships between school members.